2014
DOI: 10.1007/s12672-013-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Walking Intervention Using Mobile Technology and Interactive Voice Response on Serum Adipokines Among Postmenopausal Women at Increased Breast Cancer Risk

Abstract: Practical methods to reduce the risk of obesity-related breast cancer among high-risk subgroups are lacking. Few studies have investigated the effects of exercise on circulating adipokines, which have been shown to be associated with obesity and breast cancer. The aim of this study was to examine the effects of a walking intervention on serum adiponectin, leptin and the adiponectin-to-leptin ratio (A/L). Seventy-one overweight and obese postmenopausal women at increased risk of developing breast cancer were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Additionally, a recent meta‐analysis concluded that aerobic training significantly improved leptin levels in cancer‐free, patients with type II diabetes, which are an at‐risk population for breast cancer development . Numerous other studies have shown a reduction in leptin concentrations following exercise intervention , while others have not found significant reductions . The interventions in these latter studies, however, did not elicit significant reductions in adiposity, which may help to explain, at least in part, why no changes in circulating leptin levels were obtained.…”
Section: Mechanisms Of Exercise In Breast Cancermentioning
confidence: 98%
“…Additionally, a recent meta‐analysis concluded that aerobic training significantly improved leptin levels in cancer‐free, patients with type II diabetes, which are an at‐risk population for breast cancer development . Numerous other studies have shown a reduction in leptin concentrations following exercise intervention , while others have not found significant reductions . The interventions in these latter studies, however, did not elicit significant reductions in adiposity, which may help to explain, at least in part, why no changes in circulating leptin levels were obtained.…”
Section: Mechanisms Of Exercise In Breast Cancermentioning
confidence: 98%
“…The search identified N = 2071 potential articles from three databases: PubMed (N = 1499), CINAHL (N = 390) and SPORTDiscus (N = 182) in addition to N = 2 articles that were manually retrieved based on identified secondary analyses (Llanos et al 2014;Vroege et al 2014). Following removal of duplicates (N = 1049) and screening of abstracts and titles, 81 full-text articles were assessed for eligibility.…”
Section: Study Selectionmentioning
confidence: 99%
“…Some mobile-based delivery templates were detected in 11 chosen articles; these templates include mobile app-based (112)(113)(114)(115)(116), web-based (117)(118)(119)(120), and phone and web-based (121,122). The majority of the studies (n=8) focused on breast cancer prevention behaviors (112,(115)(116)(117)(118)(119)(120)(121), and three studies focused on screening and early detection (113,114,122). Self-care, a healthy lifestyle, and stress management are essential elements in developing healthy lifestyle interventional programs (117).…”
Section: Data Collection and Extraction Processmentioning
confidence: 99%